Education as a discipline and as an object of study: contributions to the debate - Mora-Olate, María Loreto (2020)
The aim of this essay is to give an account of a debate that still seems to be very much alive, concerning the science of education and if it is more correct to speak of "science" or "educational sciences". Through a bibliographic review, this study attempts to provide an answer to the question: how is education seen? It is concluded that, given the complexity of the educational phenomenon, to speak of "educational sciences" would not constitute subsidiarity, but rather a rational and necessary interdependence with other disciplines, enabling the study of education in its true social, historical, biological and psychological dimensions.